Leg Muscle Explosive Power and Agility to the Lay-Up Shoot Ability of Students of SMA Negeri 2 Padang - Pardian, Leni; Mariati, Sari; Erianti, Erianti (Yayasan Sekora, 2019)
The problem in this study originated from the observations that the author met in the field, it turns out that the basketball lay-up skills of SMA Negeri 2 Padang students are not very good or still low. Many factors cause the low ability of lay-up shoots, including the explosive power of the leg muscles and agility. The purpose of this study was to determine the contribution of leg muscle explosive power and agility to the lay-up shoot of basketball students of SMA Negeri 2 Padang. This type of research is correlational. The population in this study were all students of SMA Negeri 2 Padang who participated in extracurricular activities as many as 45 people. The sampling technique used purposive sampling. The sample in this study amounted to 24 female students. Data were analyzed using product moment correlation and multiple correlation and continued with the contribution by the determinant formula. Based on the data analysis, it was found that there was a contribution of leg muscle explosive power of 21.34% and agility of 19.27%, and together it was 36.12% to the basketball shoot lay up of the students of SMA Negeri 2 Padang. It was concluded that there was a contribution of leg muscle explosive power and agility to the lay-up shoot of basketball for SMA Negeri 2 Padang students. It is recommended that the trainer and students improve their physical condition exercises such as leg muscle explosive power and agility exercises.